(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to clarify the concept of green education and sustainable engineering, demonstrate the relationship between green education and sustainable development, and analyze the role of engineering education in supporting renewable energy through the integration of sustainability concepts in Libyan educational institutions. The study also highlights the concept of green education as a modern educational trend linked to sustainable development, emphasizing the importance of sustainable engineering in supporting the transition to renewable energy and reducing negative environmental impacts. The study reached several conclusions, most notably that green education represents a fundamental approach to achieving sustainable development and promoting environmental awareness within society. Furthermore, sustainable engineering plays a significant role in supporting clean energy and improving the efficiency of natural resource use. Engineering education also contributes significantly to preparing specialized expertise in renewable energy fields by integrating sustainability concepts into educational curricula, which helps develop students’ skills and fosters a culture of innovation.